PENGARUH IMPLEMENTASI GREEN ACCOUNTING DAN CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN PADA SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2023: PENGARUH IMPLEMENTASI GREEN ACCOUNTING DAN CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN PADA SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2023 - Hajarana, Hajarana; Wafa, Zaenal (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to analyze the effect of green accounting and carbon emission disclosure implementation on company value in the health sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023. The research method is quantitative with a multiple linear regression approach using secondary data from company financial and sustainability reports. The population includes 34 companies in the healthcare sector, with a purposive sample of 26 companies producing 52 observation samples. The dependent variable is company value measured by Tobin's Q, while the independent variables are green accounting and carbon emission disclosure measured by dummy variables. The results of the analysis show that green accounting has no significant effect on company value, while carbon emission disclosure has a significant negative effect. Keywords: green accounting, carbon emission disclosure, and firm value